Chambre separee in product development: vertically mediated coopetition in the automotive supply chain. (30th August 2007) - Brandes, Ove; Brege, Staffan; Brehmer, Per-Olof; Lilliecreutz, Johan
Coopetition, i.e., parallel competition and cooperation between the same companies, has many faces in the automotive industry. This paper focuses on vertically mediated coopetition in product development. The concept of 'chambre separee' is introduced as a metaphor for supplier-mediated coopetition to denote the situation when competing car manufacturers, often called OEMs, partner the same supplier in different product development projects. These projects are organisationally kept apart. When a supplier handles several development projects at the same time with different OEMs, 'chambres separees' is a way to protect Intellectual Property Rights (IPR) and allow OEM-specific solutions to be developed. But at the same time, the competitors are supporting the building of a common core competence at the First-Tier Suppliers (FTSs). The OEMs also accept some 'overhearing' from one project to another, which strengthens the supplier's knowledge base. Coopetition in this form tends to be advantageous to both OEMs and FTSs.